1985
DOI: 10.1136/bmj.291.6504.1231
|View full text |Cite
|
Sign up to set email alerts
|

Acne: double blind clinical and laboratory trial of tetracycline, oestrogen-cyproterone acetate, and combined treatment.

Abstract: Since the recent introduction of a drug regimen containing 2 mg of the antiandrogen cyproterone acetate and 50 [ig ethinyloestradiol At six months the acne (as assessed by overali grade) had improved by 68% in the antibiotic treated group and by 74% in the oestrogen-cyproterone treated group. The group given a combination of both agents improved by 82%, which was significantly better (p<0025) than the improvement in the tetracycline treated patients. No significant difference was found between the groups giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 19 publications
1
17
0
2
Order By: Relevance
“…132,133 Cyproterone acetate Cyproterone combined with ethinyl estradiol (in the form of an oral contraceptive) has been found to be effective in the treatment of acne in females. [134][135][136] Higher doses have been found to be more effective than lower doses. Cyproterone/estrogen-containing oral contraceptives are not approved for use in the United States.…”
Section: Spironolactonementioning
confidence: 95%
“…132,133 Cyproterone acetate Cyproterone combined with ethinyl estradiol (in the form of an oral contraceptive) has been found to be effective in the treatment of acne in females. [134][135][136] Higher doses have been found to be more effective than lower doses. Cyproterone/estrogen-containing oral contraceptives are not approved for use in the United States.…”
Section: Spironolactonementioning
confidence: 95%
“…Dabei beeinflusste die Konzentration des Ethinylestradiols (35 oder 50 µg) während einer Therapiedauer von 6 bzw. Die 6-monatige Behandlung einer entzündlichen Akne mit Cyproteronacetat 2 mg in Kombination mit Ethinylestradiol (50 µg) war gleich wirksam wie Tetracyclin (1 g) (74 % vs. 68 % globale Besserung der Akne; Evidenzebene 2c -eine Studie, n = 62[49]) bzw. Die 6-monatige Behandlung einer entzündlichen Akne mit Cyproteronacetat 2 mg in Kombination mit Ethinylestradiol (50 µg) war gleich wirksam wie Tetracyclin (1 g) (74 % vs. 68 % globale Besserung der Akne; Evidenzebene 2c -eine Studie, n = 62[49]) bzw.…”
unclassified
“…Percentage changes in total lesion count with CPA/EE ranged from 53.6 ± 27.5% (n ¼ 528) to 72 ± 27% (n ¼ 44) [28,30]. Greenwood et al [31] reported an 80% reduction in non-inflammatory and inflammatory lesion counts with CPA/EE (n ¼ 14) at six months. When looking more specifically at types of lesion (comedones, papules, pustules and nodules), statistically significant changes were noted at three months and final numbers of each lesion were reported as 24%, 36%, 17% and 1%, respectively relative to pretreatment (¼100%) at six months in the CPA/EE group (n ¼ 88) by Vartiainen et al [29].…”
Section: Efficacy In Acnementioning
confidence: 98%
“…For example, when combined with antibiotics (tetracycline) in the treatment of acne, or with antiandrogens (finasteride or spironolactone) in the treatment of hirsutism, the potential for enhanced efficacy was suggested [31,36,37,55]. Studies where CPA/EE was added to gonadotropin releasing hormone agonist (GnRHa) to evaluate potential for amplification of treatment response in hyperandrogenic symptoms of PCOS described significant improvement in hirsutism symptoms overall (reductions in hirsutism score were between 24% and 47.4%) but no significant difference between the two groups [50,52,56].…”
Section: Cpa/ee As Combination Treatmentmentioning
confidence: 99%
See 1 more Smart Citation